Service-Aware Algorithm Based on DT-KSVM - Hao Dong; Hua Qu; Jihong Zhao; Liangjun Chen; Huijun Dai (Dianxin kexue)
A novel service-aware method based on decision tree kernel support vector machine（DT-KSVM） algorithm was proposed.A service-aware model was developed by using ReliefF algorithm to extract service characteristics,and proposing the separable degree between samples to simply the service-aware process.Through experiment comparison between this proposed model and traditional one-versus-one SVM method,it is shown that the proposed method has a better service-aware accuracy and time performance.